1988
DOI: 10.1159/000110147
|View full text |Cite
|
Sign up to set email alerts
|

Head Injuries during One Year in a Central Hospital in Norway: A Prospective Study

Abstract: Annual age-adjusted incidence rate of head injuries in Akershus County in 1974 was estimated to be 236/100,000, 307/100,000 for males and 164/100,000 for females. The highest incidence rate occurred in males in the age group 10–19 years (489/100,000) and the lowest among females in the age group 30–39 (68/100,000). In all age groups, the incidence rate was higher in males than females. This prospective study included 488 patients, of whom 88.9% had minor head injuries and 11.1% severe head injuries. 16 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
2

Year Published

1992
1992
2007
2007

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 11 publications
3
22
2
Order By: Relevance
“…Thirty-two percent of the injuries were classified as minimal and 49% as mild. This is in accordance with other studies, reporting about 80% of hospital-referred head injuries as minor [3,4,11]. Furthermore, it has been reported that only 20% of patients with head injury are referred to the hospital [6,7].…”
Section: Severity Of Head Injurysupporting
confidence: 92%
See 2 more Smart Citations
“…Thirty-two percent of the injuries were classified as minimal and 49% as mild. This is in accordance with other studies, reporting about 80% of hospital-referred head injuries as minor [3,4,11]. Furthermore, it has been reported that only 20% of patients with head injury are referred to the hospital [6,7].…”
Section: Severity Of Head Injurysupporting
confidence: 92%
“…Our hospital admittance rate of 169/100,000 population is significantly lower than those reported in previous Norwegian studies [2,3]. This might indicate a decreasing incidence of head injuries in Norway, probably due to a decrease in road traffic accidents [13].…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…We also had no data on analgesic use, another potential confounder. We did not classify the headache 3 months after the head injury according to the diagnostic criteria of the International Headache Society, which emphasized the time between the head trauma and headache onset, because this classification was prepared several years after collection of baseline data in the present study [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Between March 10, 1974 andMarch 9, 1975 all patients admitted to the hospital with head injury were included in a prospective study [10] . Head injury was defined as trauma to the head, face or neck with at least one of the following symptoms or signs: unconsciousness, post-traumatic amnesia (PTA), skull fracture, neck fracture or head trauma combined with headache, nausea or vomiting during the first day after the accident [10] . The attending surgeon filled in a detailed registration form at admission.…”
Section: Sample and Study Designmentioning
confidence: 99%